Research progress of copper and aging-related diseases - RONG Jiahui; CAI Jiansheng; ZHANG Zhiyong (Guangxi Yike Daxue xuebao)
Copper is an essential trace element involved in a variety of biological processes, including antioxidant defense, neuropeptide synthesis, and immune function. However, copper is also a toxic metal, involved in oxidative stress and inflammation. At present, it is still unclear whether copper in the human body promotes the development of aging-related diseases. The review focuses on this topic and discusses the sources and absorption of copper in the human body, mechanisms of copper toxicity, and the effects of copper toxicity on specific aging-related diseases.